Effective and reliable platform for nonenzymatic nanomolar-range quinol detection in water samples using ceria doped polypyrrole nanocomposite embedded on graphitic carbon nitride nanosheets. (May 2021) - Ponnaiah, Sathish Kumar; Prakash, P.; Balasubramanian, Jeyaprabha
Abstract: A glassy carbon electrode modification by a novel ternary nanocomposite of advantageously united ceria, polypyrrole, and graphitic carbon nitride (CeO2 /Ppy@g-C3 N4 ) is reported here. It can be used to tailor the sensor surface for the electrochemical detection of nanomolar-level quinol (Qnl), a chemical widely used as a developing agent in photography and lithography, as a cosmetic, and as an antioxidant in rubber and food industries. The occupational exposure of Qnl may occur by inhalation or dermal contact, leading to lot of health hazards. The synthesized nanocomposite was characterized by various analytical techniques such as UV–Vis, Fourier transformed infrared (FTIR), X-ray powder diffraction, field emission scanning electron microscopy, high-resolution transmission electron microscopy, Raman, thermogravimetric analysis, energy-dispersive X-ray spectroscopy, selected area electron diffraction, and elemental mapping analyses. The oxidation current of Qnl is linear to its concentration in the range of 0.01–260 μM and the lowest detection and quantification limit are found to be 1.5 nM and 0.004 μM, respectively, with a sensitivity of 283.33 μA mM −1  cm −2 . The performance of the modified electrode was compared with those of high-performance liquid chromatography, which indicates that the proposed sensor can be used as an effective and reliable platform for nano-molar detection of Qnl in various environmental and biological fluids. Highlights: Detection of nanomolar-level quinol (Qnl) using novel CeO2 /Ppy@g-C3 N4 nanocomposite. Highly selective, sensitive, stable and fast sensing of Qnl. The sensitivity and linear range are found to be 283.33 μA mM −1  cm −2 and 0.01–260 μM respectively. The sensor is economical, reproducible and interferents-free.